Dezinstitucionalizacija - Videmšek, Petra (Socialno delo, 2015)
The article is based on authors' latest research "Evaluation of the institutional care system and the opportunities of NGOs to provide community-based services in order to achieve the process of deinstitutionalization" (2015) that was done for YHD (an NGO helping people with disabilities) and was financed by the Ministry of Public Administration of Slovenia. The starting point of the survey was to find out the possibilities for implementation of deinstitutionalization. Primarily we wanted to find out the number of persons with different kinds of disabilities aged from 18 to 65 who live in institutional care, and then explore the extent of deinstitutionalization. Further on we explored the possibilities of NGOs for implementation of the process of deinstitutionalization. We wanted to explore the users' (we consider them as experts by experience) views on living in an institution. We researched how people with personal experience of living in an institution estimate their living, which are their needs and vision for living outside the institution. The article is based on the users' point of view, on services people with disabilities receive in institutions, and on possibilities for their independent living, and what they need to achieve that goal.
Keywords: institucionalno varstvo; institutional care; osebe z ovirami; people with disabilities; uporabniška perspektiva; users' perspective; social security; dezinstitucionalizacija; living communities; socialno varstvo; samostojnost; independence